Features of the geological structure of the Achimov complex of the Yarudeisky megaswell (Western Siberia) - M. V. Osipova; R. R. Shakirov; A. G. Koshcheev; S. V. Pisarchuk; A. G. Naymushin; O. P. Nesterov (Georesursy, 2024)
This work is devoted to the peculiarities of sedimentation and geological structure of clinoform deposits of the Yarudeisky megaswell (Western Siberia). The main feature of the clinoforms under consideration is that the sediments are confined to the marginal regional clinocyclite of the western dip of the area of oncoming clinoforms, formed in relatively shallow sea conditions and differing from deep-sea clinoforms by pinching out not onto the Bazhenov formation or the early underlying clinoforms of the western dip, but by stopping their spread along the path of movement of the oncoming clinoforms eastern dip. The study of the counter clinoforms of the Yarudeisky megaswell is based on a regional analysis of the structure of cross-layered deposits in conditions of extremely poor knowledge of the study area. Within the framework of western dipping clinoforms, possible oil and gas potential prospects for the Achimov complex within the boundaries of the Yarudeisky megaswell are identified.As a result of the analysis of geological and geophysical data, the boundaries of the distribution of opposing clinoform complexes in the study area were determined. The existing paleo-geomorphological conditions that contribute to the accumulation of sandstone with improved properties in the designated seismic complexes are presented. The fields of the Nadym oil and gas bearing region with the proven productivity of the Neocomian clinoform complex are indicated, which confirms the oil and gas potential of the region and suggests favorable conditions for the accumulation of hydrocarbons in the study area.